Biological functions of miRNA-203b-3p/ZNF324 in laryngeal carcinoma: MiRNA-203b-3p alleviates the deterioration of laryngeal carcinoma - Wang, Liping; Luo, Xianyang (Cellular and Molecular Biology, 2023)
The present study aimed to elucidate the role of MicroRNA-203b-3p (miRNA-203b-3p) in protecting the deterioration of laryngeal carcinoma through targeting ZNF324. Relative levels of miRNA-203b-3p and ZNF324 in laryngeal carcinoma tissues with different tumor node metastasis (TNM) staging and pathological grades were detected. Regulatory effects of miRNA-203b-3p on clonality, viability and 5-Ethynyl-2’- deoxyuridine (EdU)-positive ratio in M2E and TU212 cells were assessed. The binding relationship between miRNA-203b-3p and ZNF324 was evaluated by dual-luciferase reporter gene assay. The involvement of ZNF324 in cell phenotype changes of laryngeal carcinoma regulated by miRNA-203b-3p was explored by rescue experiments. MiRNA-203b-3p was downregulated in laryngeal carcinoma, especially in those with advanced TNM staging or pathological grade. Overexpression of miRNA-203b-3p reduced clonality, viability and EdU-positive ratio in M2E and TU212 cells. In addition, ZNF324 was upregulated in laryngeal carcinoma, which was negatively regulated by miRNA-203b-3p. ZNF324 was verified to be the target binding miRNA-203b-3p. Notably, overexpression of ZNF324 could partially reverse the inhibitory effects of miRNA-203b-3p on laryngeal carcinoma proliferation. MiRNA-203b-3p is downregulated in laryngeal carcinoma, which blocks laryngeal carcinoma cells to proliferate through targeting ZNF324 and thus alleviates cancer progression.